Economic and Political Conditions in Indonesia Post-Perspective Reform Constitution Creation Work - Bagus Imam Faisal; Diah Retna Yuniarti; Ernawati; Sahid; Dian Eka Indriani (Proceeding International Conference on Digital Education and Social Science, 2025)
The 1998 reforms resulted in transformation in life nation and state. Efforts to improve done For overcome damage or deviations that occur during leadership President Soeharto in the New Order Era Top of Form The 1998 Reformation was a fundamental milestone in the history of national and state life in Indonesia, marking the end of the New Order regime and the beginning of the era of democratization. This normative legal research was conducted by examining various formal legal regulations. In 1998, the worsening economic conditions had a negative impact that was widely felt, with the people's welfare declining. Limited economic growth indicated serious challenges in achieving development and improving welfare. The Job Creation Law also illustrates how Indonesia positions itself in the global economic order. Regarding job creation, it is hoped that job creation will be able to absorb the widest possible Indonesian workforce amidst increasingly competitive competition and the demands of economic globalization.